Continuity and innovation in the magical tradition - Bohak, Gideon, 1961-; Harari, Yuval.; Shaked, Shaul. (Jerusalem Studies in Religion and Culture, 2011)
This volume brings together thirteen studies by as many experts in the study of one or more ancient or medieval magical traditions, from ancient Mesopotamia and Pharaonic and Greco-Roman Egypt to the Greek world, Judaism, Christianity and Islam. It lays special emphasis on the recurrence of similar phenomena in magical texts as far apart as the Akkadian cuneiform tablets and an Arabic manuscript bought in Egypt in the late-twentieth century. Such similarities demonstrate to what extent many different cultures share a "magical logic" which is strikingly identical, and in particular they show the recurrence of certain phenomena when magical practices are transmitted in written form and often preserve, adopt and adapt much older textual units.